An electromagnetic oscillation method for stress measurement of steel strands. (September 2018) - Li, Xingxing; Zhang, Benniu; Yuan, Can; Tu, Chong; Chen, Dongjun; Chen, Zhuomin; Li, Yonglin
Highlights: Nondestructive measurement on steel strands of infrastructures is important. An EMO method for stress measurement of steel strands is proposed. Oscillation frequency of the EMO sensor reflects the steel strands' stress change. Function relation between frequency and stress of the steel strand is established. Abstract: A method for stress measurement of steel strands by using electromagnetic oscillation (EMO) circuit only at its both ends, on the basis of magnetic-elastic effect, is proposed in this paper. The basic principle of EMO measurement method is presented, the circuit of EMO is designed, and the experimental system is set up. By stretching the seven-wire steel strand, the stress measurement experiments are carried out. The experimental results indicate that EMO method is an effective approach to measure the stress of steel strands, and it is expected to be used in the stress detection of the existing structures.